THE EFFECTIVENESS OF USING PODCAST FOR STUDENTS' LISTENING SKILL OF 2nd GRADE STUDENTS SMA NEGERI 6 PEMATANGSIANTAR - DEA SAHERA DAMANIK; RESI FEBRINA NAINGGOLAN; MELVA IDA MARNALA HUTAGAOL; SELVIANA NAPITUPULU (CV KULTURA DIGITAL MEDIA, 2022)
The use of technology in daily activities is increasingly attached to society. The use of internet gadgets in carrying out activities is increasingly being used. The use of technology in the field of education is also increasingly being used, one of which is the use of podcast media in helping students conduct audio-visual learning which can help SMAN 6 students in learning. The use of Podcasts as a learning medium can be used as a solution in conducting student-centered education. The use of Podcasts can show the role of technology and its derivatives in the world of education